(untitled) (Baghdad Science Journal, 2025)
The geometric morphometric technique was used to study the variables in the shape and size wings of different populations of mosquitoes Culex quinquefasciatus from different Iraqi provinces Babylon, Baghdad and Wasit. The results showed that the average of centroid size were 366, 387.5 and 407.4 Micron in Babylon, Baghdad and Kut, respectively. The statistical analysis showed that there were no significant differences in the average of centroid size of all specimens and they belong to the same species.